PUSAT PENANGKARAN HEWAN LANGKA OWA JAWA DENGAN PENDEKATAN ARSITEKTUR EKOLOGI DI BOGOR - Erick Handiana; Lily Mauliani; Anggana Fitri Satwikasari (Arsitektur UMJ, 2019)
Javan Gibbons or “Owa Jawa” are one of the endemic animals of the Java island which are included in one of the 25 most endangered primate species in the world. The rise of poaching and long-term reproductive capacity of Javan Gibbon make the population decline. One way to see Javan Gibbons is to visit a breeding place because it is hard to find in its natural habitat. Natural breeding in Indonesia is very rare and breeding that has the concept of 5 animal welfare is free from hunger and thirst, freedom from displeasure, freedom from pain is also still rare, freedom to act normally, and freedom from fear and stress. Therefore, to achieve this, there is a need for captivity that has 5 concepts of animal welfare so that the Javan gibbon population can increase. The planning and design of the rare Javan gibbon animal breeding center was designed using the concept of ecological architecture as a concept most suited to the harmony between buildings and the environment. The method of drafting the concepts used is by collecting data from related theoretical foundations and field observations, data processing, and data analysis to formulate the concepts of planning and design